Enhanced Raman scattering in graphene by plasmonic resonant Stokes emission - Ghamsari Behnood G.; Olivieri Anthony; Variola Fabio; Berini Pierre (Nanophotonics, 2014)
Exploiting surface plasmon polaritons to enhance interactions between graphene and light has recently attracted much interest. In particular, nonlinear optical processes in graphene can be dramatically enhanced and controlled by plasmonic nanostructures. This work demonstrates Raman scattering enhancement in graphene based on plasmonic resonant enhancement of the Stokes emission, and compares this mechanism with the conventional Raman enhancement by resonant pump absorption. Arrays of optical nanoantennas with different resonant frequency are utilized to independently identify the effects of each mechanism on Raman scattering in graphene via the measured enhancement factor and its spectral linewidth. We demonstrate that, while both mechanisms offer large enhancement factors (scattering cross-section gains of 160 and 20 for individual nanoantennas, respectively), they affect the graphene Raman spectrum quite differently. Our results provide a benchmark to assess and quantify the role and merit of each mechanism in surface-plasmon-mediated Raman scattering in graphene, and may be employed for design and realization of a variety of graphene optoelectronic devices involving nonlinear optical processes.